Relooking China-Russia relations through a historical lens - Char, James (2023)
Although China has not condemned President Vladimir Putin’s so-called “special military operations” in Ukraine, and the Chinese official narrative has echoed Moscow’s attribution of the war to the expansion of NATO, relations between China and Russia are not without limits. History and mutual distrust have troubled their ties in the past, and the possibility of a return to such open disagreement cannot be discounted.